Trends in 5-year community management of persons with dementia in Korea, 2003–2016 - Wonjae Sung; Hyuk Sung Kwon; Jeewon Suh; Im-Seok Koh; Keun U. Park; Hojin Choi (PLoS ONE, 2026)
Background The community 5-year management rate, defined as the proportion of patients with dementia who remain in community-based informal care without long-term institutionalization 5 years after diagnosis reflects the effectiveness of national dementia strategies and social care systems. Objective To examine national trends in the 5-year community management rate of dementia and assess whether disparities in dementia care outcomes have changed by demographic, socioeconomic, and clinical characteristics. Methods This r etrospective, population-based cohort study used a customized research database from the Korean National Health Insurance Service (2003–2021). Subgroup analyses were performed by age, sex, income, region (metropolitan vs. non-metropolitan), Charlson Comorbidity Index, diagnosing department (neurology/psychiatry vs other). The study population included patients newly diagnosed with dementia per annum during the study period. The primary outcome was the proportion of patients remaining in community 5 five years after diagnosis, without long-term institutionalization. Secondary outcomes included disparities in management rates across subgroups. Results Overall 779,558 patients were included. The 5-year community management rate showed continued improvement over time. Disparities by sex, residence, and income narrowed steadily between 2003 and 2016. Patients diagnosed in neurology or psychiatry consistently had higher management rates than those diagnosed in other departments, and this gap widened over time. Conclusions Community management rates are influenced by social and personal factors. While disparities by sex, income, and residence decreased, persistent differences by comorbidity and diagnosing department highlight the need for targeted policy interventions. The 5-year community management rate may serve as a meaningful indicator of real-world dementia care outcomes.